Maintaining differential pressure gradients does not increase safety inside modern BSL-4 laboratories - Kurth, Andreas; Weber, Udo; Reichenbacher, Detlef (Frontiers in Bioengineering and Biotechnology, 2022)
This article discusses a previously unrecognized contradiction in the design of biosafety level-4 (BSL-4) suit laboratories, also known as maximum or high containment laboratories. For decades, it is suggested that both directional airflow and pressure differentials are essential safety measures to prevent the release of pathogens into the environment and to avoid cross-contamination between laboratory rooms. Despite the absence of an existing evidence-based risk analyses demonstrating increased safety by directional airflow and pressure differentials in BSL-4 laboratories, they were anchored in various national regulations. Currently, the construction and operation of BSL-4 laboratories are subject to rigorous quality and technical requirements including airtight containment. Over time, BSL-4 laboratories evolved to enormously complex technical infrastructures. With the aim to counterbalance this development towards technical simplification while still maintaining maximum safety, we provide a detailed risk analysis by calculating pathogen mitigation in maximum contamination scenarios. The results presented and discussed herein, indicate that both directional airflow or a differential pressure gradient in airtight rooms within a secondary BSL-4 containment do not increase biosafety, and are not necessary. Likewise, reduction of pressure zones from the outside into the secondary containment may also provide sufficient environmental protection. We encourage laboratory design professionals to consider technical simplification and policymakers to adapt corresponding legislation and regulations surrounding directional airflow and pressure differentials for technically airtight BSL-4 laboratories.